2015
DOI: 10.4274/tjo.06888
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in Retinoblastoma: Current Approaches

Abstract: Retinoblastoma (RB) is the most common childhood malignant intraocular tumor. Although enucleation and external beam radiotherapy have been historically used, today the most commonly used eye-sparing approach is chemotherapy. Chemotherapy can be used in both intraocular and extraocular RB cases. Chemotherapeutic agents may be applied in different ways, including systemic, subconjunctival, intra-arterial and intravitreal routes. The main purposes of application of systemic therapy are to reduce the tumor size f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 54 publications
2
44
1
1
Order By: Relevance
“…In younger children with retinoblastoma, the potential benefit of carboplatin‐based chemotherapy can be carefully weighed against risk of ototoxicity . Multiple treatment modalities are now available that might either avoid or postpone carboplatin use at lower dosage, topotecan‐based chemotherapy, periocular chemotherapy, or intra‐arterial chemotherapy …”
Section: Discussionmentioning
confidence: 99%
“…In younger children with retinoblastoma, the potential benefit of carboplatin‐based chemotherapy can be carefully weighed against risk of ototoxicity . Multiple treatment modalities are now available that might either avoid or postpone carboplatin use at lower dosage, topotecan‐based chemotherapy, periocular chemotherapy, or intra‐arterial chemotherapy …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the survivors of retinoblastoma patients are at risk of secondary tumors. Under these circumstances, systemic chemotherapy can be used for preventing pineoblastoma and secondary cancers [22]. Several epidemiological studies have suggested that ginseng can prevent or treat many types of human malignancies [23].…”
Section: Discussionmentioning
confidence: 99%
“…Secara garis besar retinoblastoma dibagi menjadi intraokular (terbatas dalam bola mata) dan ekstraokular (ekstensi keluar bola mata mencapai jaringan lunak sekitar bola mata, sistem saraf pusat, tulang, atau KGB). 7,12 Pada tahun 2003 diperkenalkan International Classification of RB (ICRB) yang digunakan universal saat ini, sebagai prediktor keberhasilan kemoreduksi. Sistem klasfikasi TNM dari American Joint Committee on Cancer (AJCC) dan International Staging System for Retinoblastoma (ISSRB) ikut memperhitungkan keterlibatan sistemik dan esktraokular pada retinoblastoma.…”
Section: Klasifikasi Retinoblastomaunclassified